2021
DOI: 10.3390/app11041970
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Sub-Grid Scale Turbulence Model in Aeroacoustic Simulation of Human Voice

Abstract: In an aeroacoustic simulation of human voice production, the effect of the sub-grid scale (SGS) model on the acoustic spectrum was investigated. In the first step, incompressible airflow in a 3D model of larynx with vocal folds undergoing prescribed two-degree-of-freedom oscillation was simulated by laminar and Large-Eddy Simulations (LES), using the One-Equation and Wall-Adaptive Local-Eddy (WALE) SGS models. Second, the aeroacoustic sources and the sound propagation in a domain composed of the larynx and voc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 50 publications
1
11
0
Order By: Relevance
“…Figure 8 presents spectra of the full Lighthill source term together with the resolved and the SGS contribution at an arbitrarily chosen position (y = À0.15D, z = À0.73D) inside the highly turbulent region downstream of the orifice, indicated by the cross in Figure 8d. The amplitudes of the SGS contribution to the Lighthill source term are consistently one order of magnitude smaller than the resolved contribution up to frequencies of f % 10 kHz, which demonstrates their quantitative irrelevance in the full Lighthill source term, as also shown in [55]. This is also true for the case C3 with the highest Reynolds number, where the modelled unresolved part of the turbulent kinetic energy is largest.…”
Section: Source Term Analysissupporting
confidence: 57%
“…Figure 8 presents spectra of the full Lighthill source term together with the resolved and the SGS contribution at an arbitrarily chosen position (y = À0.15D, z = À0.73D) inside the highly turbulent region downstream of the orifice, indicated by the cross in Figure 8d. The amplitudes of the SGS contribution to the Lighthill source term are consistently one order of magnitude smaller than the resolved contribution up to frequencies of f % 10 kHz, which demonstrates their quantitative irrelevance in the full Lighthill source term, as also shown in [55]. This is also true for the case C3 with the highest Reynolds number, where the modelled unresolved part of the turbulent kinetic energy is largest.…”
Section: Source Term Analysissupporting
confidence: 57%
“…These fast and accurate algorithms are implemented in the open-source software openCFS (openCFS.org, [37]). Since then, several low Mach number flow applications have been addressed by computational aeroacoustics using the PCWE model successfully [5,14,23,52,60,65,69,72,182,141]. Recently, we proved that the fluid motion and acoustics can be separated inside the source region [29] and showed that the definition of the acoustic variable is valid for incompressible flows [29].…”
Section: Barriermentioning
confidence: 99%
“…They conclude from their study that turbulent structures increase the broadband component of the voice signal, supporting previous assumptions on the effect of glottal closure and glottal insufficiency. Lasota et al [9] investigate the impact of the Sub-Grid Scale (SGS) turbulence model in aero acoustic simulations. Finally, Rosenthal et al [10] investigate the mechanics of straw phonation, introducing a new electrical circuit-based model of the vocal tract as a transmission line as counterpart for CFD modelling.…”
Section: Numerical Modellingmentioning
confidence: 99%